The burial hour [large type] : a Lincoln Rhyme novel - Deaver, Jeffery (Deaver, Jeffery. Lincoln Rhyme novel., 2017)
"A businessman snatched from an Upper East Side street in broad daylight. A miniature hangman's noose left at the scene. A nine-year-old girl, the only witness to the crime. With a crime scene this puzzling, forensic expertise of the highest order is absolutely essential. Lincoln Rhyme and Amelia Sachs are called in to investigate. Soon the case takes a stranger turn: a recording surfaces of the victim being slowly hanged, his desperate gasps the backdrop to an eerie piece of music. The video is marked as the work of The Composer ... Despite their best efforts, the suspect gets away. So when a similar kidnapping occurs on a dusty road outside Naples, Italy, Rhyme and Sachs don't hesitate to rejoin the hunt. But the search is now a complex case of international cooperation--and not all those involved may be who they seem. Sachs and Rhyme find themselves playing a dangerous game, with lives all across the globe hanging in the balance"--